Doppler Echocardiographic Assessment of Pregnant Women with Chronic Arterial Hypertension - Mattia, Nádia Cristiane de [UNESP]; Barbin, Regina Lúcia [UNESP]; Borges, Vera Therezinha Medeiros [UNESP]; Peraçoli, José Carlos [UNESP]; Matsubara, Beatriz Bojikian [UNESP] (Sociedade Brasileira de Cardiologia (SBC), 2002)
OBJECTIVE: To assess structural and functional cardiac changes in asymptomatic pregnant women with chronic arterial hypertension (CAH). METHODS: One hundred pregnant women with CAH underwent conventional Doppler echocardiography. The Student t test was used to compare them with 29 normotensive pregnant women (NT) in their third gestational trimester. RESULTS: Systolic (SBP; mmHg) and diastolic (DBP; mmHg) blood pressure values were higher (p<0.001) in the CAH pregnant women (SBP: 139±19 and DBP: 92± 18) as compared with those of the NT group (SBP: 112±10 and DBP: 74±9). A significant enlargement of the left atrium (4.10±0.48 cm vs 3.6±0.3 cm; p<0.001) and of the left ventricular normalized mass (59.6±19.7 g/cm2,7 vs 41.9±3.4 g/cm2,7; p<0.001) was observed. Cardiac output (CO, L/min) and systolic volume (SV, mL) were significantly higher in the CAH group (CO: 6.0±1.54 vs 4.9±2.1, p<0.01; SV: 77.3±19.8 vs 56.5±25.8, p<0.001). CONCLUSION: Chronic hypertensive pregnant women have structural and functional cardiac changes that justify routine cardiologic assessment, even in the absence of cardiopulmonary symptoms.
Keywords: myocardial hypertrophy; ventricular function; volume overload